2008
DOI: 10.1063/1.3026706
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of local structure and electrical activation in arsenic ultrashallow junctions in silicon

Abstract: The understanding of the behavior of arsenic in highly doped near surface silicon layers is of crucial importance for the formation of N-type ultrashallow junctions in current and future very large scale integrated technology. This is of particular relevance when studying recently developed implantation and annealing methods. Past theoretical as well as experimental investigations have suggested that the increase in As concentration, and therefore the reciprocal proximity of several As atoms, leads to a drasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
1
21
1
Order By: Relevance
“…The angle of incidence was set to 0.34 • , which is well above the critical angle of external total reflection of X-rays of the selected energy and a Si substrate at ∼0.15 • . This angle was selected on the basis of the X-ray penetration depth into the substrate to ensure that the entire arsenic distribution was probed [14][15][16]. For the sample S1 an additional GI angle (∼0.05 • ) was selected to restrict the probing depth to the top 3 nm and to exclusively examine the near surface layer and the expected arsenolite crystals on the surface of the Si wafer.…”
Section: Methodsmentioning
confidence: 99%
“…The angle of incidence was set to 0.34 • , which is well above the critical angle of external total reflection of X-rays of the selected energy and a Si substrate at ∼0.15 • . This angle was selected on the basis of the X-ray penetration depth into the substrate to ensure that the entire arsenic distribution was probed [14][15][16]. For the sample S1 an additional GI angle (∼0.05 • ) was selected to restrict the probing depth to the top 3 nm and to exclusively examine the near surface layer and the expected arsenolite crystals on the surface of the Si wafer.…”
Section: Methodsmentioning
confidence: 99%
“…11). On the other hand, deactivation of As during anneal through the formation of electrically inactive complexes such as dopant-vacancy clusters was reported in ion-implanted Si [16,17]. Therefore, our results suggest that the low activation level in junctions made from As-VPD could also be explained by an important electrical deactivation of the in-diffused dopant atoms.…”
Section: Nmos With Arsenic Dopingmentioning
confidence: 49%
“…These χ j (k)'s are then fed into EXAFS fitting routines in order to compute the local structural parameters of the unknown from its experimental EXAFS data. Previous similar work on EXAFS characterization of complicated systems like layered superconductors [8][9][10] and similar EXAFS modeling and analysis work on the dopant-related electrically inactive structures in semiconductors [11][12][13][14][15][16] proved that with careful theoretical modeling and the EXAFS data analysis and interpretation could lead to crucial information about the subtle structural modifications under pressure, ion implantation and post annealing [17][18][19].…”
Section: Exafs Data Analysismentioning
confidence: 90%
“…This is of peculiar relevance when studying novel implantation and annealing methods. Past theoretical as well as experimental investigations have suggested that the increase of As concentrations, and therefore the vicinity of the dopant atoms, leads to a drastic increase of electrically inactive defects giving only marginal effects on reducing sheet resistance [11]. Monoclinic SiAs clusters, as well as various arsenic-vacancy aggregates contribute to the deactivation of the arsenic.…”
Section: Local Structural Information In Arsenic Ultra Shallow Junctimentioning
confidence: 99%
See 1 more Smart Citation